Pengaruh Penerapan Safety Management System Oleh Personel Apron Movement Control Terhadap Tingkat Keselamatan Di Sisi Udara Di Bandar Udara Internasional Yogyakarta - Vindi Aditia Yudha Pratama; Ary Subiyantoro; Budiono Sulistyadi (LPPM AKADEMI MANAJEMEN ADMINISTRASI YOGYAKARTA, 2025)
This study aims to determine the effect of the implementation of a safety management system (SMS) by Apron Movement Control personnel on airside safety at Yogyakarta International Airport. This study used a quantitative research method, selecting a population of 34 AMC employees. Data analysis techniques used validity tests, reliability tests, and simple regression analysis. Hypothesis testing used a t-test and the level of relationship between variables was determined using R-test. The t-test results obtained a calculated t-value > t-table (6.664 > 2.0369), indicating that SMS implementation significantly influences airside safety. Based on the results, the regression equation Airside Safety (Y) = 12.718 + 0.598 SMS Implementation (X) indicates that SMS implementation influences airside safety. The coefficient of determination test yielded an R-square value of 0.580. This means that the SMS implementation variable influences airside safety at Yogyakarta International Airport by 58.0%, while the remaining 42.0% is influenced by other causal factors originating from outside this regression method.